A total systems study on Company ABC - Carrido, Roselle Nicole D.; Mangasing. Patrick Christian R.; Oria, Alfrey S.; Sapina, Patricia Ann L.; Tamayao, Mili-Ann M. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
In the recent years, the fashion retail has grown with the different needs of the changing trends of fashion and the developing desire of fashion customers for the retail industry's speed and value. This study primarily aims to elicit a significant improvement in the company's management and inventory system after thorough documentation of the current system. It also provides an outside perspective on the company's operations and processess and provide solutions in problems concerning the administration, procurement, inventory, marketing, and finances of the company through the proposed design alternatives. Company ABC is a fashion materials and tailoring supplies distributor, wholesaler, and retailer operating in Metro Manila. The company started as a small store in 1967 at Libertad Street, Pasay City and currently has two branches: one in Dian St. Makati and the other in Market! Market! They offer more than 10,000 individual products which include fabrics, laces, ribbons, hats, masks, and other clothing materials which are sourced from both local and foreign suppliers. The scope of the study only focused on measurements concerning fabrics, which accounts for 42% of the total sales of the company. Further analysis of the sales and inventory system were limited by the lack of data per stock keeping unit (SKU), and the deletion of records by the company's previous accountant. The latter explains the availability of data used in the analysis which were from 2016 to 2018 only. In this total systems study, a number of documentation tools were used by the researchers to analyze the total sales of the company. A swim lane chart and SIRPORC diagram were used to show the work movement between the departments and demonstrate the interaction of the different processes from ordering to customer sale. Documents from 2016 to 2018 such as the balance sheet and income statement were used for the computation of financial ratios for problem analysis. From the 2018 balance sheet, the quick ratio dropped to 0.297 when the Php40-M was recorded. Company ABC was also computed to have an inventory turnover of 0.15 in 2018, which means that the company takes 6.8 years to sell and replace its inventory during a cycle. Problem exploratory tools such as the 5-Why Analysis and Ishikawa Diagram were used to identify the pain points on the operations of the company. Through these tools, it was identified that the management and methods section of the company must be evaluated. It was then formulated that the company has an inventory problem as seen through the 6-year turnover period and percent inventory to asset ratio of around 75%. To make things worse, there is also an outstanding loan payable of Php40 million, pressuring the company's capability to meet its short term liabilities. To address these issues, there were 4 proposed design alternatives working hand-in-hand. The forecasting and marketing design alternatives may directly solve the problem on low inventory turnover. Forecasting results will provide forecasted values on demand so the company will be able to have a proper guide on how much they should order while the marketing plan provides a projected increase in the total sales after the maximization of the online channel of the company. However, in order to have more specific and reliable values per product, especially for forecasting, the company needs to have a computerized inventory tracker that will speed up their inventory tracking with less errors and enable them to store these data to calculate for Reorder Point and Economic Order Quantity. In addition to this, to address the problem they had that led to revering back to manual inventory system which is the lack of personnel who will manage the computerized tracker, organizational restructuring was done to define specific employee tasks and designate a Procurement and Inventory Manager that will handle the new tracker. After implementation, the company had more informed product purchases and no reports on work overlaps across departments. Following the Holt-Winters forecasting model made and only purchasing 20% of the forecasted demand will increase the inventory turnover from 0.15 to 0.21 times a year. This means that instead of turning over every 6.8 years, the company will turnover every 4.8 years instead. The company will have net income of around 9 million, which already takes into account operating expenses. A decrease of about 22.5% in the loan payable, which is now at 31 million from the original 40 million pesos in loans, will also be obtained after tackling 42% of the inventory. Tracking one SKU per day was reduced from approximately 350.40 seconds or (-6 minutes) to 23.05 seconds, saving 93.42% of the manager's time. They will now also be able to track 1250 SKUs per day. Marketing is expected to bring in an extra 13% in sales per year, which aids in lessening the debt. This leads to a total increase of Php 1,884,403 in the company's sales per year. Also, the company is expected to have around 4 to 5 sale transactions online and around 6 to 7 daily page visits after the proposed marketing plan.
Feasibility study.
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design.
Keywords: Company ABC; System analysis; Fashion design